Congenital bilateral scrotal agenesis with bilateral cryptorchidism: a case report - Ram Jeewan Singh; Bijay Kumar Suman; Keerthana Bachala; Amit Kumar Sinha; Bindey Kumar (International Journal of Contemporary Pediatrics, 2023)
Congenital bilateral scrotal agenesis is very rare anomaly and characterized by the absence of scrotal rugae. It may be associated with other extra-genital anomalies as a part of a syndrome. Etiology is unknown but may be due to primary failure of labioscrotal folds development or secondary to localized 5-alpha-reductase type 2 deficiency. Various surgical techniques used for neoscrotum construction with different types of complications. In index case, we performed bilateral orchidopexy without creating neoscrotum.